Spatio-temporal evolution of rockfall activity from 2007 to 2011 at the Piton de la Fournaise volcano inferred from seismic data - Hibert, Clément; Mangeney, Anne; Grandjean, Gilles; Peltier, Aline; DiMuro, Andrea; Shapiro, Nikolai M.; Ferrazzini, Valérie; Boissier, Patrice; Durand, Virginie; Kowalski, Philippe (Journal of volcanology and geothermal research, 2017)
Seismic data have been used to catalog the location and volume of most of the rockfalls that occurred at the Piton de la Fournaise volcano from May 2007, just after the major collapse of the Dolomieu summit crater floor, to May 2011. This catalog made it possible to compare the evolution of the number and volume of rockfalls at a high temporal resolution and to investigate their links with eruptions, seismicity, deformations and rainfalls affecting the Piton de la Fournaise volcano. Results show that the purge of unstable areas created by the Dolomieu crater floor collapse occurred in two phases: a first phase, lasting three months, during which the intense rockfall activity immediately following the collapse decreased abruptly and a second phase, lasting more than two years, during which the daily volume of the rockfalls slowly decreased before reaching a steady state. A detailed study of 4 time periods, including 3 eruptive cycles, indicates that strong seismicity can increase the number of rockfalls. Furthermore, when a dike reaches the surface at the summit of the central cone, giving birth to an eruption, the associated local forcing can in some cases increase the volume of rockfalls, possibly by creating or expanding weak zones. In most cases, this is not observed for dike intrusions that do not reach the surface. The newly created weak zones are most often far from the eruptive fissures of the ongoing eruption, but close to the location of the next eruption. This suggests that these distant zones are also weakened at depth, thus creating preferred paths for future dikes propagating toward the surface. The impact of rainfall on rockfall activity was also studied, given that La Réunion Island is subject to very intense rainfall events. Our results show that rainfall can in some cases trigger rockfalls rapidly, with response times of less than a day, but not systematically, and no triggering rainfall threshold was found. •Seismic methods allow to retrieve the location and the volume of rockfalls that occurred at Piton de la Founraise Volcano during a period of 4 years•We investigated the influence of seismicity, eruptions, deformation and rainfalls on the rockfall activity•We show that for most of the summit eruptions an increase in the number and the volume of rockfalls is observed•Spatial concentration of rockfall activity during an ongoing eruption might indicate where the next summit eruption will occur•Rainfall can increase the rockfall activity, but not systematically, and no triggering rainfall threshold was found